Mechanically induced thermal runaway severity analysis for Li-ion batteries. (May 2023) - Lin, L.S.; Li, J.L.; Fishman, I.M.; Torres-Castro, L.; Preger, Y.; De Angelis, V.; Lamb, J.; Zhu, X.Q.; Allu, S.; Wang, H.
Abstract: Thermal runaway is one of the most important safety concerns in the deployment of Li-ion batteries. We developed a standardized single-side indentation test protocol to induce an internal short-circuit. Cell voltage, temperature, and applied compressive force are monitored as a function of time. Each cell is given an observed hazard severity (OHS in five categories) modified from the EUCAR table. Meanwhile a calculated hazard severity (CHS) is obtained solely based on temperature and voltage curves. The calculation formula considers the cell temperature, rate of temperature increase, cell capacity, state of charge (SOC), voltage drop, and voltage drop rate. Each term is assigned with an appropriate weight to scale the calculated score from 0 to100. This method was applied to >100 Li-ion batteries with various SOCs and chemistries, and their OHS and CHS were displayed against SOC. The purpose is to provide battery designers, manufacturers, and end-users a clear comparison of thermal runaway severity of different batteries. Highlights: A standardized single-side indentation test protocol was developed. Severity scores were calculated from Cell Temperature and voltage vs Time curves. >100 Li-ion batteries with various SOCs and chemistries were tested. The calculated scores provide a clear comparison of thermal runaway severity.